Early-Onset Alzheimer Disease (EOAD) With Aphasia: A Case Report - Borges, Marcus Kiiti; Lopes, Thais Nakayama; Biella, Marina Maria; Siqueira, Alaíse; Mauer, Sivan; Aprahamian, Ivan (Frontiers in Psychiatry, 2018)
Background: Alzheimer’s disease (AD) is traditionally subdivided into early onset (EOAD) and late onset (LOAD). EOAD has an onset before age 65 years and accounts for 1–5% of all cases. Two main presentation types of AD are familial and sporadic. Case presentation: The authors present the case of a 68-year-old retired white man, with a college level educational background. At 55 years of age, the patient presented cognitive decline with short-term memory impairment and slowed, hesitant speech. At 57 years, he was unable to remember the way to work, exhibiting spatial disorientation. PET-CT: revealed hypometabolism and atrophy in the left temporal lobe and posterior region of the parietal lobes. Disease course: Evolving with difficulties in comprehension and sentence repetition over past 3 years and with global aphasia in past 6 months, beyond progressive memory impairment. Discussion: Possibly due to the young age and atypical presentation, and the diagnosis of EOAD is often delayed. To the best of our knowledge, this case can be classified as a sporadic EOAD with aphasia. Clinical variant and neuroimaging findings were crucial to the diagnosis and treatment of this atypical presentation of AD.